2019
DOI: 10.1097/mao.0000000000002192
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cochlear Coverage on Auditory and Speech Performance in Cochlear Implant Patients

Abstract: Objective: To determine the effect of cochlear coverage on audiological and speech parameters in patients with cochlear implants. Previous work has investigated the effect of tailoring electrode size to a cochlear implant recipient's individual cochlear duct length (CDL). However, no clear relationship has been found between speech development and the extent of electrode insertion, and the benefits of apical stimulation are not yet clear. Methodology: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
1
9
1
1
Order By: Relevance
“…The best speech perception is reported in a CC between 70 and 75% [ 15 ]. This is in line with earlier studies that could not find a benefit from very deep insertion [ 16 , 17 ]. A too short electrode insertion may lead to poorer functional outcomes [ 18 ].…”
Section: Introductionsupporting
confidence: 93%
“…The best speech perception is reported in a CC between 70 and 75% [ 15 ]. This is in line with earlier studies that could not find a benefit from very deep insertion [ 16 , 17 ]. A too short electrode insertion may lead to poorer functional outcomes [ 18 ].…”
Section: Introductionsupporting
confidence: 93%
“…Concerning the observed significant difference of CDL in male and female patients in the present study, other studies also found longer cochleae in male individuals [27,44,45]. Contributing to the difference might be correlation to a larger height in the individual or a larger head diameter, which has not been investigated so far.…”
Section: Discussioncontrasting
confidence: 65%
“…This finding was inconsistent with previous studies such as that by Akin et al, 15 in which no significant difference was reported between boys and girls among 37 patients. Similarly, no significant difference was observed between boys and girls in the study by Doubi et al 16 where the cochlear duct lengths of 97 patients, 47 of whom were female, were examined by CT Scans and patient CAP scores were evaluated within a three-year interval. The present study appears to be the first to reveal such a difference between boys and girls, however, there was no significant difference in our study data to justify this difference.…”
Section: Discussionmentioning
confidence: 90%